Phase-matched second-harmonic generation due to thermal expansion of T1GaSe2 layered crystal - Seyidov, MirHasan Yu.; Suleymanov, Rauf A.; Salehli, Ferid (Elsevier, 2012)
Second-harmonic generation effects have been investigated in TIGaSe2 layered crystal over a temperature range where ferroelectric phase exists. Pronounced periodical changes of the second-harmonic signal with temperature have been discovered. The observed effect is explained within the phase synchronism condition which changes with the temperature. The main mechanism of the thermal expansion of the sample in the observed phenomenon is explained. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Second-harmonic generation; Phase synchronism; Linear thermal expansion; Phase transition